SISTEM INFORMASI PENGOLAHAN DATA PENYELENGGARAAN SKRIPSI MAHASISWA MENGGUNAKAN METODE WATERFALL (STUDI KASUS IAIN BATUSANGKAR) - Khairunnisa, Khairunnisa; Defiariany, Defiariany; Rohandi, Keukeu (Sainstek : Jurnal Sains dan Teknologi, 2020)
To facilitate the processing of thesis management reports, reports assignments, minutes and attendance, an application is needed. Dealing with these needs, an analysis of the processing of student thesis data processing needs to be done so that results and requirements can be obtained for the application that is need. The analysis was carried out by analyzing the needs, users and facilities needed by the application. The result of this study was the data processing information system for organizing student thesis using the waterfall method. There are 5 stages that were carried out in order to obtain maximum results, namely Communication (Project Initiation & Requirements Gathering), Planning (Estimating, Scheduling, Tracking), Modeling (Analysis & Design), Construction (Code & Test), and Deployment (Delivery, Support, Feedback). The finding showed that this application helps facilitate the processing of thesis implementation data and displays the information needed by Batusangkar State Islamic Institute users.